Soil macroinvertebrates alter the fate of root and rhizosphere carbon and nitrogen in a turfgrass lawn. (September 2020) - Bray, Natalie; Thompson, Grant L.; Fahey, Timothy; Kao-Kniffin, Jenny; Wickings, Kyle
Abstract: Soil invertebrates, especially larger macroinvertebrates, move soil, fragment organic matter and change resource accessibility for soil microorganisms. Macroinvertebrates also affect the formation and turnover of aggregates, which are important controls of soil organic matter dynamics because they physically protect organic matter from degradation and influence many belowground processes ranging from microbial activity to nutrient sorption and water flow. We still lack a complete understanding of how different soil invertebrate functional groups affect the incorporation of root derived carbon and nitrogen into belowground pools. We assessed the effects of macroinvertebrates on soil aggregate abundance and composition and quantified the fate of organic matter derived from roots using a two-year macroinvertebrate exclusion-based field mesocosm study coupled with stable isotope labeling in a turfgrass lawn ecosystem. We hypothesized that macroinvertebrates change soil aggregates dynamics by increasing macroaggregates and decreasing microaggregates and enhancing the incorporation of root-derived organic matter into macroaggregates. We found that within the turfgrass root zone, macroinvertebrates increased the proportion of macroaggregates and decreased free microaggregates. In addition, macroinvertebrates increased carbon and nitrogen incorporation into macroaggregates, microaggregates and coarse particulate organic matter, detected via isotopic enrichment of those soil fractions. We found that macroinvertebrates affect the fate of recently fixed root- and rhizodeposit-derived organic matter in a turfgrass lawn ecosystem, and particularly its incorporation into soil aggregates, similar to findings in forest and agricultural systems. Highlights: Macroinvertebrates affect SOM dynamics within the rhizosphere of a turfgrass lawn. Macroinvertebrates incorporate root material selectively into aggregates. The structure and function of belowground biota affect carbon and nitrogen cycling.